轧机主传动轴系扭振固有频率计算的有限元法 - 黄晓刚; 蹇开林 (Jixie chuandong)
The nature frequency and the torque amplitude factor of torsion vibration of simple shafting and gear-driven shafting are calculated by using finite element method, the validity of the finite element method to calculate the torsion vibration of shaft system is testified by comparing with Lump mass method. Finally, the torsion vibration nature frequency and torque amplitude factor of a rolling mill are calculated by using finite element method.